Underwater noise impact assessment of a wave energy converter in the northern Atlantic (Spain) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
As most nations around the world commit to decarbonize their economies, the electrification of many sectors is an ongoing trend that will only strengthen in the next years. The energy demands for this transition are considerable, and renewable energies are being pushed to substitute fossil-fuel technologies with great urge.While marine renewable energy (MRE) is still not as developed as wind, hydraulic or photovoltaic energies, it constitutes a promising and mostly untapped resource. MRE may complement quite well the production curves of both wind and solar power, and can provide non-fossil energy to coastal populations, or those located in islands where land is precious, so its development is important to many countries, given that most of the population is located near the coast.Even though MRE does not produce CO2 emissions, their possible impacts on the marine environment are already well theorized, such as encounters with moorings/cables, collisions, underwater pollution (among others) there are still uncertainties in the actual impacts of real WECs on their surrounding ecosystem.This is one of the reasons behind the European research project SafeWAVE - Streamlining the assessment of environmental effects of wave energy (2020-2023), - as well as its predecessor WESE – Wave Energy in Southern Europe (2018-2021)-, which is dedicated to research on the non-technological barriers to the development of the wave energy sector. A fundamental work package of SafeWAVE is the monitoring and modelling of possible relevant impacts of wave energy converters (WEC), including electromagnetic fields, underwater noise, or seabed integrity, using as test cases four different WECs deployed in corresponding test sites, located in Basque Country (Spain), Nantes (France) and Aguçadoura (Portugal).The aim of the present work is to report the results obtained from monitoring, processing, and modelling of underwater noise around one of the wave energy converters (WEC) studied in the context of this project. The monitoring activities consisted of two campaigns, one before and during installation of the device, and another one during its operation and eventual decommissioning. Each one covered a duration of about 45 days, using one and three moored hydrophones surrounding the WEC, respectively. Acquired data was processed and analysed to obtain Sound Pressure Levels (SPL) in 1/3 octave bands ranging from 20 Hz to 20 kHz for different sea states, operational status, and activity (deployment, decommission, etc.). Lastly, underwater transmission losses were modelled using a full range dependent computational model allowing to assess the extent of acoustic disturbance that could be caused by the WEC, and furthermore, by a hypothetical array of several WECs.Initial results evidence differences between the SPL distributions before and after the deployment of moorings, as well as during operation (with respect to background levels), at the location of the hydrophones.